The Illustrated Wavelet Transform Handbook : Introductory Theory and Applications in Science, Engineering, Medicine and Finance, Second Edition /: Introductory Theory and Applications in Science, Engineering, Medicine and Finance, Second Edition. (2017) - Addison, Paul S
No abstract available